The red herring in the cerebrospinal fluid: Aspergillus niger isolation in a 9-year case of recurrent lymphocytic meningitis - C. Gopalakrishnan, Gowtham Kishore; Asokan, Anil Kumar; Somasekaran, Harikrishnan; B., Jose P.; Sreehari, Sreedhanya; Eapen, Aby C.; Jose, Jyotsna M.; Radhakrishnan, Lekshmi; Pillai, Vidya R.; B. Suresh, Neethu (International Journal of Research in Medical Sciences, 2026)
Invasive central nervous system (CNS) aspergillosis is classically a disease of the severely immunocompromised host, driven by rapidly progressive and often fatal infection. Aspergillus niger, an intrinsically rare neuropathogen even within this context, has scarcely been reported as a causative agent of meningitis. We report a 41-year-old man with chronic alcohol and tobacco use who presented with fever, headache, and photophobia two days after returning to Kerala, India, from Saudi Arabia. His records documented six identical meningitis episodes over nine years (2016, 2017, 2019, 2020, 2021, and 2025), each resolving completely with empirical antimicrobials and without neurological sequelae. Lumbar puncture revealed lymphocytic pleocytosis (85 cells/cumm, 98% lymphocytes), mildly elevated protein (59 mg/dL), and borderline-normal glucose (46 mg/dL). Extensive workup including Brucella serology, Weil-Felix test, TB PCR, Interferon-Gamma Release Assay, and autoimmune panels were negative. Unexpectedly, cerebrospinal fluid culture isolated Aspergillus niger. Empirical acyclovir and ceftriaxone were commenced; voriconazole was added following culture identification. The patient improved rapidly and was discharged, but was lost to follow-up before planned skull-base CT imaging could be completed. This case presents a compelling diagnostic dilemma: whether the isolate represents true invasive infection, periodic trans-cribriform antigenic seeding from a chronic sinus mycetoma, or an incidental finding superimposed on a benign recurrent meningitis syndrome such as Mollaret's meningitis or Neuro-Behçet's disease. It underscores the importance of integrating longitudinal clinical context when interpreting unexpected microbiological results, and of maintaining a broad differential rather than anchoring on a single laboratory finding.